Communicative Compentences in EFL Learning - Rama Dwika Herdiawan (Journal of English Language Learning, 2018)
Abstract: In terms of communication, it requires a number of competences that develop the cognitive as well as metacognitive skills. This deals with the communicative competences which lead to the effectiveness of not only having communication but also acquiring the knowedge inside it. Thus, this study is concerned with how the communicative competences (Celce Murcia, 2007) influence the students’ cognitive and metacognitive skills in terms of learning English. The findings reveal that they way they communicate should reflect the socio-cultural norms of the target language (English) and they also have different background in terms of learning English as well as knowledge in understanding how to communicate using English politely. In addition, the students closely engage with how to construct the written or spoken text. In this case,  they need to have the relevant schemata in terms of selecting, sequencing, and also arranging the words, phrases, clauses, sentences, and also utterances in order to create unified information to convey in the context of communication. In brief, communicative competences reflect a number of cources in order to educate learners to be leading and professional.Keywords: communicative competences, EFL Learning